Professional sports and crime: do professional hockey games increase city-level crime rates? - Block, Kristina (Crime & delinquency, 2021)
Previous research has found that sports games increase certain crimes including theft and vandalism, but the relationship between sports and other offenses such as motor vehicle theft, robbery, and assaults is mixed. Using regular season National Hockey League (NHL) game data and city-level, incident-level crime data from four large U.S. cities, this paper estimates if professional ice hockey games played at home is associated with increases in property crimes, alcohol-related crimes, and assaults during and right after games the over course of four NHL seasons. Results show that NHL games lead to small but significant increases in property crimes and assaults. There is no significant effect for alcohol-related crimes. Implications and suggestions for future work are discussed.